Doing business in India : a framework for strategic understanding - Lakshman, C. (Elsevier Asian studies series., 2015)
A comprehensive look at understanding India with a strategic framework that can be readily used for doing business in this market is needed. Doing Business in India discusses the cultural and consumer profile of the people of India and how these fit into the macroeconomic context. The analytical framework provided and illustrated with real case examples spans domains such as the institutional context of the country (full of voids and amazing peculiarities) and the interesting federalist political framework in a country with many states. Based on this foundation, the book introduces the busine.